Whole genome sequence and annotation dataset of rare actinobacteria, Barrientosiimonas humi gen. nov., sp. nov. 39T from Antarctica ... : تسلسل الجينوم الكامل ومجموعة بيانات التعليقات التوضيحية للبكتيريا الشعاعية النادرة، Barrientosiimonas humi gen. nov.، sp. nov. 39T من القارة القطبية الجنوبية ... - Sin Yee Chong; Aida Azrina Azmi; Yoke Kqueen Cheah (OpenAlex, 2023)
Barrientosiimonas humi gen. nov., sp. nov. 39T is a rare actinobacteria strain isolated from the less explored extreme environment of the Antarctic soil. Here, we present the whole genome sequencing and annotation data from the high-quality draft genome of B. humi from Antarctica. The extracted genomic deoxyribonucleic acid (DNA) was sequenced using the PacBio Sequel sequencing platform, followed by the Illumina HiSeq sequencing system. Subsequently, the assembly data from Canu 1.7 and Pilon were subjected to bioinformatics analysis for genome annotation to analyze the entire genomic information of the sequences. Different bioinformatics analysis approaches were used to disclose a high-quality draft genome basis for B. humi and provided a better understanding of its biological and molecular functions. Note that 83,639 reads were predicted from its 3.6Mb genome size, with a guanine-cytosine content (GC) content of 72.39%. The genome was assembled into two contigs, where the larger contig represents the ... : Barrientosiimonas humi gen. nov.، sp. nov. 39T هي سلالة شعاعية نادرة معزولة عن البيئة المتطرفة الأقل استكشافًا في تربة القارة القطبية الجنوبية. هنا، نقدم تسلسل الجينوم الكامل وبيانات التعليقات التوضيحية من مسودة الجينوم عالية الجودة لـ B. humi من القارة القطبية الجنوبية. تم تسلسل حمض الديوكسي ريبونوكليك الجيني المستخرج (DNA) باستخدام منصة تسلسل PacBio Sequel، متبوعًا بنظام تسلسل Illumina HiSeq. في وقت لاحق، خضعت بيانات التجميع من Canu 1.7 و Pilon لتحليل المعلوماتية الحيوية للتعليق التوضيحي للجينوم لتحليل المعلومات الجينية الكاملة للتسلسلات. تم استخدام مناهج تحليل المعلوماتية الحيوية المختلفة للكشف عن أساس جينوم مسودة عالية الجودة لـ B. HUMI ووفرت فهمًا أفضل لوظائفها البيولوجية والجزيئية. لاحظ أنه تم التنبؤ بـ 83،639 قراءة من حجم الجينوم 3.6 ميجابايت، مع محتوى جوانين- سيتوزين (GC) بنسبة 72.39 ٪. تم تجميع الجينوم في متجاورين، حيث يمثل المتجاور الأكبر الكروموسوم ويمثل المتجاور الأصغر البلازميد. وهو يتألف من 3381 جينًا مشفرًا، مع شرح حوالي 95 ٪ منها وظيفيًا. وهو يتألف من 3318 تسلسل ترميز، وجين tmRNA واحد، و 57 ...